UNIT LINKED: LIFE INVESTMENT INSURANCE (Academicia Globe: Inderscience Research, 2021)
The article describes the theoretical bases of investment life insurance, including the advantages and disadvantages of Unit Linked insurance products. Given reviews on foreign experience of Unit Linked Life Insurance product as well as perspectives for its implementation and development in our country.